The Mediating Role of Green Innovation in Islamic Banking between Green Finance and Green Sustainability Performance - Al-Refai, Omima; Al-Zaqeba , Murad Ali Ahmad; Jarah, Baker Akram Falah (International Journal of Energy Economics and Policy, 2026)
Analyzing the interplay between finance, green sustainability performance, and the RBV and DCT within the context of Jordanian Islamic banks, the work creates a conceptual model that constitutes the transformation of resource innovation and financially ethical sustainability outcomes. The Islamic banks' employees’ surveys, quantitatively analyzed using Smart PLS 4 and the PLS-SEM approach, endorsed the proposed model. The findings proved green finance and innovation to be the positive catalysts of sustainability performance and green innovation, respectively, thereby providing direct proof of the PLS-SEM paradigm. Additionally, the findings describe green innovation as a complete mediator of the green finance and sustainability performance paradigm. Conclusively, green innovation is the instrumental model for banks for the conversion of positive financial instruments into positive social and ecological impacts. The Islamic banks, sustainability strategists, and policy formulators translate Islamic and direct net positive financial instruments principles into an innovation platform that generates green transformation. Conceptually, the work integrated the PR and DCT paradigm into the green Islamic finance domain and the Islamic net positive financial principles, resource transformation and innovation.